2005
DOI: 10.1176/appi.ps.56.5.576
|View full text |Cite
|
Sign up to set email alerts
|

Medical Advance Care Planning for Persons With Serious Mental Illness

Abstract: Although persons with serious and persistent mental illness have little experience with medical advance care planning, they show substantial interest in it. Furthermore, they are able to consider and communicate their preferences. This study supports the feasibility, acceptability, and utility of a standardized approach to medical advance care planning with this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 57 publications
0
91
0
Order By: Relevance
“…The most common concerns were: financial burden on family or loved ones; emotional burden on loved ones; being in pain and suffering; interpersonal issues such as leaving family and friends; funeral and disposition of the person's body; and spiritual concerns. 5 Most participants believed that someone should be designated to make health care decisions for a person who is too sick to do so. 5 Foti's research also supports the "feasibility, acceptability and utility of a standardized approach to medical advanced care planning."…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common concerns were: financial burden on family or loved ones; emotional burden on loved ones; being in pain and suffering; interpersonal issues such as leaving family and friends; funeral and disposition of the person's body; and spiritual concerns. 5 Most participants believed that someone should be designated to make health care decisions for a person who is too sick to do so. 5 Foti's research also supports the "feasibility, acceptability and utility of a standardized approach to medical advanced care planning."…”
Section: Resultsmentioning
confidence: 99%
“…5 Most participants believed that someone should be designated to make health care decisions for a person who is too sick to do so. 5 Foti's research also supports the "feasibility, acceptability and utility of a standardized approach to medical advanced care planning." 5 While there are potential benefits to advance directives, such as supporting autonomy and enhancing communication, and while many jurisdictions have advance care legislation and guidelines in place with court-ordered precedent for them to be respected, 29 there may be institutional or legal impediments to advance care planning for people with SPMI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, a report from the U.S. Government noted that 10 to 25% of Americans had an AMD (U.S. Government Accountability Office, 1995). Later studies have reported AMD documentation in less than 20% of the U.S. general public (DeLuca, 2000), 19% of patients with cancer (Dy et al, 2010), 26% of medical-surgical inpatients (Salmond & David, 2005), 18% of mentally ill persons (Foti, Bartels, Merriman, Fletcher, & Van Citters, 2005), 70% of community-dwelling older adults (Teno, Gruneir, Schwartz, Nanda, & Wetle, 2007), and 35% of nursing home residents (Bradley, Wetle, & Horwitz, 1998).…”
Section: Introductionmentioning
confidence: 99%